THE ROLE OF R&D EXPENDITURES IN ECONOMIC GROWTH RATE; A CROSS-COUNTRY STUDY - Ali Hassan Zadeh; Hassan Heidari (فصلنامه پژوهش‌های اقتصادی ایران, 2001)
Research and Development expenditures in process of development and progress of economies are very important. Therefore this paper tries to determine effect of R&D expenditures on economic growth rate in the set of different countries of the world. This study has estimated the causal relation between GNP growth rate, and R&D expenditures, fiscal investment, and growth rate of labor force of countries during 1991-95. By using the World Bank data, we have estimated our model for groups of high income and lower income countries. We found that the R&D activities have significant and great effect on GNP growth rate in all countries, especially in developing countries.